Perbandingan Efektivitas Persiapan Persalinan antara Media Offline dan Online Menggunakan Lembar Balik dan Leaflat di Era Pandemi Covid-19 - Tridiyawati, Feva (Jurnal Ilmiah Bidan (JIB), 2023)
In this COVID-19 pandemic situation, the government has formed a policy of limiting almost all routine services, one example of which is maternal and neonatal health services and other health care facilities. This results in the emergence of anxiety from pregnant women so that they delay carrying out pregnancy tests. The research method used in this research is using a quasi-experimental method with a comparative method (comparison). The location in this study was carried out at the Puskesmas Kel. Jatibening whose address is at Jl. Amaryllis RT/RW 002/012 Kel. Jatibening district. Pondok Gede, Bekasi City, West Java 17412, in its implementation the research was carried out during August 2021. Sampling in this study used Accidental Sampling, as many as 30 samples. The purpose of this study is to find out the Comparison of the Effectiveness of Childbirth Preparation between Offline and Online Media Using Flip Sheets and Leaflets in the Era of the Covid-19 Pandemic. The results of the study on pregnant women in preparation for childbirth after being given counseling with online media using a good flip sheet of 83.33% compared to offline counseling which was 73.33%, as many as 73.33% of pregnant women after offline counseling were good in preparing for childbirth, compared to 70% of pregnant women who were given counseling using online media used leaflets. Based on the results of the research above, it can be seen that online delivery preparation counseling using flipcharts is more effective than online media using leaflets with test results p <0.05 (p = 0.073).